2021
DOI: 10.1155/2021/5298006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs 340-5p, 92a-3p, and 381-3p in Patients with Endometriosis: A Plasma and Mesenchymal Stem-Like Cell Study

Abstract: Background. Endometriosis is the most prevalent gynecological disease with elusive etiology. The mysterious entity and the lack of noninvasive diagnostic methods affect women’s lives negatively. This study is aimed at finding the relationship between miR-340-5p, 92a-3p, and miR-381-3p and the pathogenesis of endometriosis in endometrial mesenchymal stem-like cells (eMSCs) of endometriosis and assessing their potential as a noninvasive biomarker in plasma. Methods. Peripheral blood and eMSC specimens were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 72 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…MiR-7 plays a role in trophoblasts' invasion via the TGF-β-Smad pathway [ 58 ]. MiR-92a-3p plays a role in endometriosis [ 59 ] and is associated with endometrial receptivity [ 60 ] and trophoblast invasion [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-7 plays a role in trophoblasts' invasion via the TGF-β-Smad pathway [ 58 ]. MiR-92a-3p plays a role in endometriosis [ 59 ] and is associated with endometrial receptivity [ 60 ] and trophoblast invasion [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second predicted miRNA by the BioMAI predicting system was miR-92a-3p which is associated with a higher success of blastocyst implantation [ 20 , 54 ]. The level of miR-92a-3p was also studied in the cases of endometriosis and PCOS [ 55 , 56 ] where the level was downregulated. Endometriosis, as well as PCOS, is a well-known reason for infertility that reduces the implantation rate after embryo transfer [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, vascular endothelial growth factor; HIF1, hypoxiainducible factor-1; TGFβ, transforming growth factor-beta; ECM, extracellular matrix; MMPs, matrix metalloproteinases; RBC, red blood cell (EMT)-pro-angiogenic factors, and it can also facilitate other tumorigenesis mechanisms such as genome instability. 34,54,55 Although fibroblasts, immune cells, and endothelial cells produce a large portion of pro-inflammatory signals as tumor microenvironment components, they have also been shown to play an important role in tumorigenesis promotion through the secretion of cytokines and proteases from CAFs. 34 It has been shown that fibroblasts adjacent to the CRC cells express IL-6, FAPα, and SPINK3 as an inflammation-induced factor in CRC.…”
Section: Inflammation As a Potential Mechanism In Tumorigenesismentioning
confidence: 99%
“…One of the most important promoters of tumorigenesis in colon cancer is inflammation 53 . Inflammation starts as a response of the immune system to pathogens or tissue damage; however, perpetuating this response results in increasing the incidence of cancer due to the weakness of the anti‐tumor response because it can release bioactive molecules from tumor microenvironment cells such as chemokines, cytokines, and growth factors—that contribute to constant proliferation and cell survival signals to prevent apoptosis‐metalloproteinases,—as a modifier of extracellular matrix to initiate epithelial‐mesenchymal transition (EMT)—pro‐angiogenic factors, and it can also facilitate other tumorigenesis mechanisms such as genome instability 34,54,55 . Although fibroblasts, immune cells, and endothelial cells produce a large portion of pro‐inflammatory signals as tumor microenvironment components, they have also been shown to play an important role in tumorigenesis promotion through the secretion of cytokines and proteases from CAFs 34 …”
Section: The Molecular Mechanisms Behind the Microenvironment In Tumo...mentioning
confidence: 99%